Novel Approaches in the Inhibition of IgE-Induced Mast Cell Reactivity in Food Allergy - Tontini, Chiara; Bulfone-Paus, Silvia (Frontiers in Immunology, 2021)
Allergy is an IgE-dependent type-I hypersensitivity reaction that can lead to life-threatening systemic symptoms such as anaphylaxis. In the pathogenesis of the allergic response, the common upstream event is the binding of allergens to specific IgE, inducing cross-linking of the high-affinity FcRI on mast cells, triggering cellular degranulation and the release of histamine, proteases, lipids mediators, cytokines and chemokines with inflammatory activity. A number of novel therapeutic options to curb mast cell activation are in the pipeline for the treatment of severe allergies. In addition to anti-IgE therapy and allergen-specific immunotherapy, monoclonal antibodies targeted against several key Th2/alarmin cytokines (i.e. IL-4Rα, IL-33, TSLP), active modification of allergen-specific IgE (i.e. inhibitory compounds, monoclonal antibodies, de-sialylation), engagement of inhibitory receptors on mast cells and allergen-specific adjuvant vaccines, are new promising options to inhibit the uncontrolled release of mast cell mediators upon allergen exposure. In this review, we critically discuss the novel approaches targeting mast cells limiting allergic responses and the immunological mechanisms involved, with special interest on food allergy treatment.